Franco-british military and political cooperation after the gold war - Кравченко, В. В. (International relations and international law Journal, 2016)
The article discusses bilateral military-political relations of Great Britain and France in the period of the postbipolar system of international relations. On some episodes of historical milestones of the twentieth century, such as the Suez crisis, as well as political events of 1990-2000’s, such as the unification of Germany, the Iraqi campaigns, the Balkans conflicts, the general line of cooperation between the two nations as well as the loyalty to transatlantic values are illustrated. It is analyzed some aspects of bilateral cooperation in the field of security and defense after the cold war, which became reality thanks to the «process of Saint-Malo» and the signing of The Lancaster House Treaties.